Varieties of contested multilateralism: positive and negative consequences for the constitutionalisation of multilateral institutions - Christian Kreuder-Sonnen; Bernhard Zangl (Global constitutionalism, 2016)
This essay analyses the consequences of contested multilateralism (CM) for the level of constitutionalisation of specific multilateral institutions. We argue that CM has implications for institutions' constitutional quality in particular if it is polity-driven and not (merely) policy-driven, that is, when actors' employment of alternative institutions stems from their dissatisfaction with the political order of an institution rather than individual policies. Given the co-existence of constitutionalised and non-constitutionalised multilateral institutions in today's international order, state and non-state actors can use alternative institutions to contest the constraining or discretionary character of an institution's polity. We hold that CM is likely to have negative consequences for the constitutionalisation of multilateral institutions if it is employed `top-down' by states to enhance their freedom to wield discretionary authority, but that it is likely to have positive consequence if it is employed `bottom-up' by society actors to constrain the exercise of discretionary authority through multilateral institutions. We illustrate the empirical plausibility of our claims in two cases involving top-down contestation of the European Economic and Monetary Union (EMU) and bottom-up contestation of the World Health Organization (WHO).
Additional information: Dieser Beitrag ist mit Zustimmung des Rechteinhabers aufgrund einer (DFG-geförderten) Allianz- bzw. Nationallizenz frei zugänglich / This publication is with permission of the rights owner freely accessible due to an Alliance licence and a national licence (funded by the DFG, German Research Foundation) respectively.
Keywords: 330; constitutionalisation; international authority; multilateral institutions; regime complexity; regime shifting